MiR-10a-5p-Mediated Syndecan 1 Suppression Restricts Porcine Hemagglutinating Encephalomyelitis Virus Replication - Hu, Shiyu; Li, Zi; Lan, Yungang; Guan, Jiyu; Zhao, Kui; Chu, Dianfeng; Fan, Gencheng; Guo, Yuguang; Gao, Feng; He, Wenqi (Frontiers in Microbiology, 2020)
Porcine hemagglutinating encephalomyelitis virus (PHEV) is a single-stranded RNA coronavirus that causes nervous dysfunction in the infected hosts and leads to wide-spread alterations in the host transcriptome by modulating specific microRNA (miRNA) levels. MiRNAs contribute to RNA virus pathogenesis by promoting antiviral immune response, enhancing viral replication, or altering miRNA-mediated host gene regulation. Thus, exploration of the virus-miRNA interactions occurring in PHEV-infected host may lead to the identification of novel mechanisms combating the virus life cycle or pathogenesis. Here, we discovered that the expression of miR-10a-5p was constitutively up-regulated by PHEV both in the N2a cells in vitro and mice brain in vivo. Treatment with miR-10a-5p mimics allowing miR-10a-5p enrichment and resulted in a significant restriction in PHEV replication, suggesting widespread negative regulation of the RNA virus infection by miR-10a-5p. The outcomes were also evidenced by miR-10a-5p inhibitors over-expression. Luciferase reporter, qRT-PCR, and western blotting analysis further showed that Syndecan 1 (SDC1), a cell surface proteoglycan associated with host defense mechanisms, acts as a target gene of miR-10a-5p during PHEV infection. Naturally, siRNA-mediated knock-down of SDC1 leads to a reduction in viral replication, implying SDC1 expression is likely to favorable conditions for viral replication. Together, the findings demonstrated that the abundant miR-10a-5p leads to downstream suppression of SDC1 and it functions as an antiviral mechanism in the PHEV-induced disease, providing a potential strategy for the prevention and treatment of PHEV infection in the future work.